Improvement of Ethanol Production in Saccharomyces cerevisiae by High-Efficient Disruption of the ADH2 Gene Using a Novel Recombinant TALEN Vector - Ye, Wei; Zhang, Weimin; Liu, Taomei; Tan, Guohui; Li, Haohua; Huang, Zilei (Frontiers in Microbiology, 2016)
Bioethanol is becoming increasingly important in energy supply and economic development. However, the low yield of bioethanol and the insufficiency of high-efficient genetic manipulation approaches limit its application. In this study, a novel transcription activator-like effector nuclease (TALEN) vector containing the left and right arms of TALEN was electroporated into Saccharomyces cerevisiae strain As2.4 to sequence the alcohol dehydrogenase gene ADH2 and the hygromycin-resistant gene hyg. Western blot analysis using anti-FLAG monoclonal antibody proved the successful expression of TALE proteins in As2.4 strains. qPCR and sequencing demonstrated the accurate knockout of the 17 bp target gene with 80% efficiency. The TALEN vector and ADH2 PCR product were electroporated into ΔADH2 to complement the ADH2 gene (ADH2+ As2.4). LC–MS and GC were employed to detect ethanol yields in the native As2.4, ΔADH2 As2.4, and ADH2+ As2.4 strains. Results showed that ethanol production was improved by 52.4 ± 5.3% through the disruption of ADH2 in As2.4. The bioethanol yield of ADH2+ As2.4 was nearly the same as that of native As2.4. This study is the first to report on the disruption of a target gene in S. cerevisiae by employing Fast TALEN technology to improve bioethanol yield. This work provides a novel approach for the disruption of a target gene in S. cerevisiae with high efficiency and specificity, thereby promoting the improvement of bioethanol production in S. cerevisiae by metabolic engineering.